2019
DOI: 10.3390/ijms20030691
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in Flavivirus Infections

Abstract: Virus infections of the central nervous system (CNS) can manifest in various forms of inflammation, including that of the brain (encephalitis) and spinal cord (myelitis), all of which may have long-lasting deleterious consequences. Although the knowledge of how different viruses affect neural cells is increasing, understanding of the mechanisms by which cells respond to neurotropic viruses remains fragmented. Several virus types have the ability to infect neural tissue, and astrocytes, an abundant and heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 130 publications
(221 reference statements)
3
79
0
2
Order By: Relevance
“…induced by multiple stressor agents and neuroinflammatory conditions, such as bacterial and viral infections, neurodegenerative diseases and acute trauma 51 . Viral antigens can lead to an inflammatory environment that, through microglia activation, culminate to astrocytic reactivity 21 . During the active state, astrocyte morphology and cytoskeleton protein expression are altered, showing hypertrophy, higher number of cytoplasmic processes and increased expression of intermediate filaments, especially GFAP, usually detected by increased marker intensity 52 .…”
Section: Zikv Infection Induces Glial Reactive State Reactive Gliosimentioning
confidence: 99%
“…induced by multiple stressor agents and neuroinflammatory conditions, such as bacterial and viral infections, neurodegenerative diseases and acute trauma 51 . Viral antigens can lead to an inflammatory environment that, through microglia activation, culminate to astrocytic reactivity 21 . During the active state, astrocyte morphology and cytoskeleton protein expression are altered, showing hypertrophy, higher number of cytoplasmic processes and increased expression of intermediate filaments, especially GFAP, usually detected by increased marker intensity 52 .…”
Section: Zikv Infection Induces Glial Reactive State Reactive Gliosimentioning
confidence: 99%
“…The histopathological results of this study showed that the brain tissue of mice in the JEV group and the JEV + Rapa group had obvious vascular in ammation and late glial cell proliferation, while the mice in the JEV + Wort group and the JEV + CQ group had slight vascular in ammatory response and obvious glial cell proliferation, other groups of mice showed normal. JEV infection leads to excessive microglia activation and the subsequent release of numerous pro-in ammatory cytokines, resulting in an in ammatory storm [27][28]. In order to attempt to further con rm that autophagy inhibitors can alleviate the vascular in ammatory responses of brain tissues in JEV-challenged mice, we observed that IL-6, IL-1β, and TNF-α were signi cantly downregulated in the brain tissues of JEV-challenged mice treated with autophagy inhibitors compared with those of the JEV and JEV + Rapa groups.…”
Section: Discussionmentioning
confidence: 99%
“…JE is an in ammatory disease of the central nervous system. JEV infection can cause excessive activation of microglia in the brain and, in turn, release of a large number of pro-in ammatory cytokines such as IL-6, TNF-α, and RANTES, which promote the migration and penetration of numerous white blood cells into the brain, resulting in an in ammatory storm that causes severe damage to the brain tissues [27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Foci of neuronal infection were observed in the cortex, hippocampus, cerebellum, basal ganglia or the anterior horn of the spinal cord [148]. Neurons and astrocytes are infected with WNV and TBEV [142,149,150]. Following neuronal cell death, inflammatory molecules (such as IL1-β, IL6, IL8 and TNFα) have potentially toxic effects on uninfected neurons.…”
Section: Tbev and LIVmentioning
confidence: 99%